2018
DOI: 10.1111/sjtg.12270
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of drought in the Kerio Valley Basin, Kenya using the Standardized Precipitation Evapotranspiration Index: 1960−2016

Abstract: The Kerio Valley basin in Kenya has undergone several periods of drought, yet drought patterns in the region are not well understood due to limited climatic data. Drought events in the region have resulted in crop failure and livestock deaths, exacerbating food shortages. In this study, the Standardized Precipitation Evapotranspiration Index (SPEI), a multi‐scalar drought index was used to examine the onset, duration, severity, intensity, and frequency of agricultural and hydrological drought in the region. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…It is constructed from precipitation, temperature, and potential evapotranspiration and can be calculated on a variety of time scales [41]. Recently, SPEI has been widely used in many fields, such as climate change, environmental quality assessment, and drought assessment [42]. The key concept of SPEI is to describe the degree of drought in an area by calculating how far the difference between precipitation and potential evapotranspiration deviates from the average state.…”
Section: Standardized Precipitation Evapotranspiration Indexmentioning
confidence: 99%
“…It is constructed from precipitation, temperature, and potential evapotranspiration and can be calculated on a variety of time scales [41]. Recently, SPEI has been widely used in many fields, such as climate change, environmental quality assessment, and drought assessment [42]. The key concept of SPEI is to describe the degree of drought in an area by calculating how far the difference between precipitation and potential evapotranspiration deviates from the average state.…”
Section: Standardized Precipitation Evapotranspiration Indexmentioning
confidence: 99%
“…However, due to the different subjects and purposes, researchers have proposed numerous drought indices. As listed in the technical report of the World Meteorological Organization (WMO, 1975;2016), there are as many as 58 drought indices from different countries (Wang et al, 2019). Among the many indices, the PDSI (Palmer, 1965), SPI (McKee et al, 1993), and SPEI (Vicente-Serrano et al, 2010a) are widely used.…”
Section: Speimentioning
confidence: 99%
“…Drought can typically be characterized by four characteristics: duration, severity, intensity, and frequency (Mishra and Singh, 2010;Kimosop, 2019). The calculation methods are as follows: Zero was used as the criterion to determine whether drought occurred in this study (as shown in Table 1); i.e., when the SPEI was less than 0, this value indicated the occurrence of drought.…”
Section: Characteristics Of Droughtmentioning
confidence: 99%
“…At present, SPEI is often estimated globally through station observations [12][13][14] or climate datasets released by climate research organizations [1,9,10,[15][16][17][18][19][20]. However, the detailed spatial patterns of SPEI cannot be obtained from these sources because of the current low densities of weather stations and the low spatial resolutions (e.g., >50 km per grid cell) of climate datasets [21,22].…”
Section: Introductionmentioning
confidence: 99%